Elisabeth Christine und Friedrich der Grosse - Noack, Paul,Elisabeth Christine,Friedrich (Klett-Cotta, 2001)
Rez.: Erscheint: 1. September 2001
9783608942927
Keywords: Biografie; Frederick; Elisabeth Christine; Friedrich